Desenvolvimento de alevinos de trairão (Hoplias lacerdae) na ausência de luz - Salaro, Ana Lúcia; Luz, Ronald Kennedy; Sampalo Zuanon, Jener Alexandre; Sirol, Rodolfo Nardez; Sakabe, Róberson [UNESP]; Garcia de Araújo, Wagner Azis; Souto, Eduardo Ferri (Universidade Estadual de Maringa, 2006)
Sixty-six trairão (Hoplias lacerdae) fingerlings (average weight of 2.0±0.5 g and total length of 5.8±0.2 cm), trained to accept dry rations, were allotted to six 15-L aquariums, with aeration and controlled temperature (24.0±0.5°C), in a density of 0.7 juveniles/L, aiming to evaluate the effects of darkness on fish productive performance. The treatments consisted of two photoperiods: 12 hours light: 12 hours dark (12L:12D) and 0 hour light: 24 hours dark (OL:24D), with three replicates. Fingerlings were fed ad libitum a commercial extruded diet (42% CP), twice a day. The aquariums were cleaned daily for excrement withdrawal through siphoning, exchanging 1/4 total volume. At the end of the experiment (30 days), weight gain, feed:gain ratio and survival and cannibalism rates were evaluated. The results showed that darkness did not affect the productive performance of trairão juveniles.
Development of trairão (Hoplias lacerdae) fingerlings in darkness
Keywords: Hoplias lacerdae; Photoperiod; Trairao; aeration; controlled study; darkness; fish; nonhuman; photoperiodicity; pisciculture; water temperature; Hoplias